On deflection worm routing on meshes - Roberts, A.; Symvonis, A. (IEEE First ICA³PP, IEEE First International Conference on Algorithms and Architectures for Parallel Processing, Brisbane, Australia, 19-21 April, 1995, 1995)
In this paper, we consider the deflection worm routing problem on two dimensional n/spl times/n meshes. Our results include: (i) an off-line algorithm for routing permutations in O(kn) steps, and (ii) a general method to obtain deflection worm routing algorithms from packet routing algorithms.< >